The Rearing of Clown Loach (Chromobotia macracanthus) Larvae by Using Enriched Live Foods - . Chumaidi; . Nurhidayat; A. Priyadi (Jurnal Akuakultur Indonesia)
The enrichment of natural live  food with unsaturated fatty acid can increase survival and growth rate of fish larvae. The purpose of  this experiment was to know the effect of various natural live food with or without nutrient enrichment on survival and growth rate of clown loach (Chromobotia macracanthus) larvae.  The experiment was done indoor by using plastic jars filled 5 L water and aerated continuously.  Twenty clown loach larvae of four days old, 5.58 ± 0.12   mm in average length,  were stocked in plastic jars and  were reared for 28 days. The treatment were: a) Artemia nauplii as control;  b) rotifer without enrichment;  c) enriched rotifer, d) Moina nauplii without enrichment, and e) enriched Moina nauplii.  As enrichment agent, we used 200 mg of tuna eggs powder and 200 mg of baker's yeast which dissolved and  aerated in 2 L of water for one hour.  Proximate analysis for amino  and fatty acids content were done before the treatment, at 5 days old and at 32 days old (juvenile).  The result showed that higher survival (80.00%) and growth rate (average body length 12.80±1.85 mm) could be achieved by feeding clown loach larvae with enriched Moina nauplii.